Membangun Komunikasi Digital dengan Pemustaka UPT Perpustakaan Universitas Andalas (Unand) sebagai Penciptaan Ekosistem Digital - Syahrial Nupin, Iswadi (Ikatan Pustakawan Indonesia, 2023)
This study aims to explain the strategic steps taken to create a digital ecosystem at UPT Library Unand. The analytical method used in this study is a qualitative research method. The technique of taking the subject in this study used a purposive sampling technique, namely the sampling technique of data sources with certain considerations. The results showed that conveying messages to library users through Facebook, Instagram and Zoom Meeting was relatively ineffective because the use of digital platforms was not managed properly. there is no special staff that manages the digital communication platform. Therefore, staff with a Bachelor of Visual Communication Design (DKV) and D4 Software Engineering background are needed to manage digital communication platforms.